EVALUASI KUALITAS AIR SUNGAI BATANGHARI DI AREA PENAMBANGAN PASIR DESA SEMBUBUK (MUARO JAMBI) BERDASARKAN WATER QUALITY INDEX (WQI - Rahmadini, Zananta; Gusri, Lailal; Damris (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2026)
Sand mining activities from riverbeds or banks can harm the environment, especially water quality, by increasing turbidity, which can endanger ecosystems and human health. This study aims to analyze the water quality of the river around the sand mining area using the Water Quality Index (WQI) method. In this study, water samples were collected at three points: upstream, middle, and downstream, with three repetitions conducted over three consecutive days near the sand mining area of Sembubuk Village, Muaro Jambi Regency. The test results showed significant values in several parameters, including TSS at the midpoint, which reached 252 mg/l. This figure indicates a high number of suspended particles in the water. The turbidity value at the midpoint was also very high, at 285 NTU, indicating very cloudy water. In addition, the DO level at the midpoint of the mining site was the lowest, at 2.21 mg/l. This low DO indicates that the mining process releases oxidized materials trapped in the bottom sediment, which consume oxygen in the water. These parameters individually did not meet the river water quality standards. The method used combined various parameters, and the overall value could reflect the combined conditions of each parameter. Thus, the analysis of the WQI pollution level of the Batanghari River around the sand mining area in Sembubuk Village, Muaro Jambi Regency, indicated that the pollution level was at